Depressive disorders in Brazil: results from the Global Burden of Disease Study 2017 - Cecília Silva Costa Bonadiman; Deborah Carvalho Malta; Valéria Maria de Azeredo Passos; Mohsen Naghavi; Ana Paula Souto Melo (BMC, 2020)
Abstract Background Depression is one of the major causes of disability worldwide. The objective of this study was to analyze the results of the Global Burden of Disease Study 2017 (GBD-2017) for depressive disorders in Brazil and its Federated Units (FUs) in 1990 and 2017. Methods We used GBD-2017 study methodology to evaluate the prevalence estimates, the disability-adjusted life-year (DALY), and the years lived with disability (YLDs) for depressive disorders, which include major depressive disorder and dysthymia. The YLD estimates and the position of these disorders in the DALY and YLD rankings were compared to those of seven other countries. The observed versus expected YLD, based on the sociodemographic index (SDI), were compared. Results In GBD-2017, the prevalence of depressive disorders in Brazil was 3.30% (95% uncertainty interval [UI]: 3.08 to 3.57), ranging from 3.79% (3.53 to 4.09) in Santa Catarina to 2.78% in Pará (2.56 to 3.03), with significant differences between the Federated Units. From 1990 to 2017, there was an increase in number of YLD (55.19%, 49.57 to 60.73), but a decrease in the age-standardized rates (− 9.01%, − 11.66 to − 6.31). The highest proportion of YLD was observed in the age range of 15-64 years and among females. These disorders rank 4th and 13th as leading causes of YLD and DALY, respectively, in Brazil. In the other countries evaluated, the ranking of these disorders in the YLD classification was close to Brazil's, while in the DALY classification, there was higher variability. All countries had YLD rates similar to the overall rate. The observed/expected YLD ratio ranged from 0.81 in Pará to 1.16 in Santa Catarina. Morbidity of depressive disorders was not associated with SDI. Conclusions Depressive disorders have been responsible for a high disability burden since 1990, especially in adult women living in the Southern region of the country. The number of people affected by these disorders in the country tends to increase, requiring more investment in mental health aimed at advancements and quality of services. The epidemiological studies of these disorders throughout the national territory can contribute to this planning and to making the Brazilian health system more equitable.